Massive peritoneal cavity calcification in the course of advanced ovarian cancer: a case report - Wójcik, Gustaw; Piskorz, Jolanta; Bulikowski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2015)
Ovarian cancer usually does not give any clinical signs until it reaches a large size. This condition is often associated with the occurrence of metastases within the peritoneal cavity, pelvic and abdominal cavities. Ovarian cancer can spread by intraperitoneal implantation, by way of the lymphatic system, and also through the systemic circulation. Even when the tumor reaches a large size, the symptoms are not specific and may resemble other ailments. Therefore, ovarian cancer is detected in most cases only in the third and fourth level of advancement.Peritoneal calcification occurs in many diseases. The degree of calcium deposits is usually small and does not give clinical symptoms.In the reported case, computed tomography of the abdomen showed numerous scattered peritoneal calcifications of irregular shape as well as massive calcification in the uterus and appendages. In the detection of changes associated with calcification, multidetectory computed tomography shows a very high sensitivity. It makes the precise location and assessment of the extent of changes possible.